2015
DOI: 10.1039/c4ra13830a
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanostars as SERS-active substrates for FT-Raman spectroscopy

Abstract: Surfactant-free and CTAB-stabilized gold nanostars were synthesized. Their FT-SERS activity was tested. A nanomolar limit of detection and a Raman enhancement factor of more than 105 were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…In general, EF can be obtained by Raman measurements by considering the first factor in Eqn , along with a correction through a shielding coefficient K shielding , which takes into account the propagation of incident and scattered radiations through the colloid (second factor in Eqn ): EF=[]IitalicSERSCitalicsolIitalicRamanCitalicsurf1Kshielding()λinc…”
Section: Resultsmentioning
confidence: 99%
“…In general, EF can be obtained by Raman measurements by considering the first factor in Eqn , along with a correction through a shielding coefficient K shielding , which takes into account the propagation of incident and scattered radiations through the colloid (second factor in Eqn ): EF=[]IitalicSERSCitalicsolIitalicRamanCitalicsurf1Kshielding()λinc…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the peak average dimension of the obtained nanoparticles is ≈130.3 nm [see the scanning electron microscope (SEM) image in the central panel of Figure 1 e]. As shown by the solid blue curve in Figure 1 b, a strong absorption peak of 96.2% was obtained at the wavelength of 661 nm with the 80% absorption band from 414 to 956 nm (or 70% absorption band from 407 to 1083 nm, demonstrating its potential application for SERS up to 1064 nm [41][42][43] , which is signifi cantly broader than the previous report. [ 24 ] It has been reported that by manipulating the effective optical constants of ultrathin vanadium dioxide layer on sapphire, perfect optical absorption can be obtained with a given layered thin-fi lm interferometer structure.…”
Section: Resultsmentioning
confidence: 90%
“…Raman spectroscopic analysis was performed on the electrodeposited electrodes, and the resulting spectra are shown in Figure 3 b,c. Generally, the intensity of Raman signals is positively dependent on particle size [ 33 ], specific surface area [ 34 ], and the probability of SERS-active sites [ 35 ]. The spectrum of AgNF/ITO electrodes displayed peaks at 642.7, 741.2, 930.7, 1058.59, 1380, 1587, 1774, 2124.25, and 2439 cm −1 .…”
Section: Resultsmentioning
confidence: 99%